The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.yhbeh.2020.104803
|View full text |Cite
|
Sign up to set email alerts
|

The effect of HF-rTMS over the left DLPFC on stress regulation as measured by cortisol and heart rate variability

Abstract: The prefrontal cortex, and especially the Dorsolateral Prefrontal Cortex (DLPFC), plays an inhibitory role in the regulation of the Hypothalamic-Pituitary-Adrenal (HPA) axis under stressful situations. Moreover, recent evidence suggests that a sustained DLPFC activation is associated with adaptive stress regulation in anticipation of a stressful event, leading to a reduced stress-induced amygdala response, and facilitating the confrontation with the stressor. However, studies using experimental manipulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 77 publications
1
28
0
Order By: Relevance
“…However, we did not observe a significant relationship between perceived stress and RSFC. The DLPFC is thought to play an inhibitory role in the physiological response to stress via regulation of amygdala projections to hypothalamus, a key region of the HPA-axis known to be modulated by GABAergic activity in response to stress (23,51,52). The DLPFC has been targeted in neurostimulation treatment aimed at improving stress-related cognitive impairments and physiological responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not observe a significant relationship between perceived stress and RSFC. The DLPFC is thought to play an inhibitory role in the physiological response to stress via regulation of amygdala projections to hypothalamus, a key region of the HPA-axis known to be modulated by GABAergic activity in response to stress (23,51,52). The DLPFC has been targeted in neurostimulation treatment aimed at improving stress-related cognitive impairments and physiological responses.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the PFC tonically inhibits subcortical sympathoexcitatory circuits (e.g., Thayer et al., 2009), it was hypothesized that inactivation of the dlPFC using transcranial magnetic stimulation (TMS) should be associated with greater HR, lower HRV, and larger cortisol responses to a perseverative cognition induction compared to inactivations of a motor brain region or sham stimulation. These researchers indeed found that dlPFC inactivation was associated with higher HR, lower vagally mediated HRV, and greater cortisol responses that extended into the recovery period compared to the other conditions (see also Angius et al., 2019; De Witte et al., 2020; Pulopulos et al., 2020). These findings provide compelling evidence for the relationships among the PFC, and autonomic and endocrine stress responses.…”
Section: Cortical Activity Hrv and Stress/emotion Regulationmentioning
confidence: 89%
“…Concerning the objective biological salivary cortisol measurements, our results did not show differential effects in both groups. Most of the studies focused on left dorsolateral prefrontal cortex stimulation and suggested rTMS [69,70] or tDCS [71] could reduce the neuroendocrine response to stress in healthy subjects. Nevertheless, recently, a study evaluating a single session of tDCS on the left dlPFC in healthy subjects showed that tDCS was probably responsible for an attenuation of the autonomic response to stress (heart rate variability) without a significant reduction in cortisol concentration [72].…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the ground, participants were invited to get into the elevator and were asked to rise as high as possible. At each floor (1,3,5,13,22,35,55,70 and 99, for a total of 9 levels and a 150 m maximum height), the door opened, and participants had to cross a wooden plank between two platforms in order to access the elevator of the second part of the skyscraper and be able to go up to the next floor (Figure 5). Once the board was crossed, participants had to observe their environment for 30 s before rating the SUD twice with a 30 s interval between both.…”
Section: Exposure Sessions (V2 and V3)mentioning
confidence: 99%